Psychological Effects of Digital Media Consumption on Youth Behavior and Mental Well-Being (Al-Aasar, 2024)
Digital media has significantly influenced the social, educational, and psychological dimensions of young people’s lives. The increasing availability of smartphones, social media platforms, and online entertainment content has introduced substantial changes in the daily routines and behavioral patterns of youth. This research study aims to examine the relationship between digital media consumption and the mental well-being of young individuals. Recent studies indicate that prolonged use of social media may be associated with mental health concerns such as depression, anxiety, low self-esteem, and social isolation. At the same time, digital media also plays a constructive role by providing access to information, facilitating social connectivity, and creating educational opportunities for young users. This study explores both the positive and negative impacts of digital media and highlights strategies for responsible and balanced digital media use in order to support and improve the mental health of youth.